An anthrax "smoke" detector. - Lester, E.D.
We report a method for automated monitoring of airborne endospores, which combines an aerosol capture technique with endospore detection based on terbium luminescence turn-on. We have demonstrated quantification of aerosolized bacterial spores with a response time of ~15 min, a sensitivity of 104 spores/ml, and a dynamic range of 4 orders of magnitude using a bioaerosol sampler, a microwave, and a lifetime-gated fluorimeter. Ultimately, the most attractive feature we have demonstrated is the unattended monitoring of aerosolized bacterial spores for the duration of a workday (~8 hours)
Keywords: 15 min; 8 h; Aerosol capture technique; Aerosolized bacterial spores; Airborne endospores; Anthrax smoke detector; Automated monitoring; Bioaerosol sampler; Dynamic range; Endospore detection; Lifetime-gated fluorimeter; Microwave; Quantification; Response time; Sensitivity; Terbium ions; Terbium luminescence turn-on.; Unattended monitoring; Workday